2003
DOI: 10.3171/foc.2003.15.4.10
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine-induced attenuation of brain edema and neurological deficits in a rat model of intracerebral hemorrhage

Abstract: Object In the authors' previous studies they found that brain iron accumulation and oxidative stress contribute to secondary brain damage after intracerebral hemorrhage (ICH). In the present study they investigated whether deferoxamine, an iron chelator, can reduce ICH-induced brain injury. Methods Male Sprague–Dawley rats received an infusion of 100 μl of autologous whole blood into the right basal gang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
135
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(144 citation statements)
references
References 32 publications
7
135
0
2
Order By: Relevance
“…In support of this possibility, several investigators have shown that nonselective inhibitors of heme oxygenase (tin-mesoporphyrin IX, tin-protoporphyrin, and zinc protoporphyrin) decreased ICH-induced brain injury, including brain edema and neurologic deficits (Gong et al, 2006;Huang et al, 2002;Koeppen et al, 2004;Wagner et al, 2000). Deferoxamine, a ferric iron chelator, was shown to have a similar neuroprotective effect after ICH (Nakamura et al, 2004a;Wan et al, 2006). These findings suggest that ROS could be a potential target for ICH therapy.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 74%
“…In support of this possibility, several investigators have shown that nonselective inhibitors of heme oxygenase (tin-mesoporphyrin IX, tin-protoporphyrin, and zinc protoporphyrin) decreased ICH-induced brain injury, including brain edema and neurologic deficits (Gong et al, 2006;Huang et al, 2002;Koeppen et al, 2004;Wagner et al, 2000). Deferoxamine, a ferric iron chelator, was shown to have a similar neuroprotective effect after ICH (Nakamura et al, 2004a;Wan et al, 2006). These findings suggest that ROS could be a potential target for ICH therapy.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 74%
“…Further, Richard Keep, Guohau Xi, and coworkers have extensively studied the effects of DFO in autologous blood infusion model of intracerebral hemorrhage and subarachnoid hemorrhage rat models and reported that DFO posttreatment reduces the brain nonheme iron concentration, iron-handling protein expression, oxidative stress, brain edema, neuronal death, and behavioral deficits in rat and piglet models (Nakamura et al, 2004;Gu et al, 2009;Okauchi et al, 2010;Lee et al, 2010).…”
Section: Hypoxia-inducible Factor Prolyl Hydroxylase Inhibition As Anmentioning
confidence: 99%
“…Second, in the adult brain, excess iron can be rapidly sequestered by upregulated iron storage proteins such as ferritin, transferrin, and ceruloplasmin (Patel et al, 2002;Regan et al, 2002;Rouault, 2001). Although iron regulatory capacity may be overwhelmed in the setting of injury, which explains why iron chelators such as deferoxamine have showed neuroprotective benefits (Goldstein et al, 2003;Nakamura et al, 2004). Third, some evidence suggests a role for HO-1 in facilitating the transport of iron out of cells.…”
Section: Heme Oxygenase As Modulator Of Neural Injurymentioning
confidence: 99%